Training and Coaching Strengthening Character Education Based On School Culture InThe Upper Class Of Madrasah Ibtidaiyah Nurul Islam Tamidung Batang-Batang: Pelatihan Dan Pembinaan Penguatan Pendidikan Karakter Berbasis Kultur Sekolah Di Kelas Atas Madrasah Ibtidaiyah Nurul Islam Tamidung Batang-Batang - Ali Armadi; Muhammad Misbahudholam AR; Kurratul Aini (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this service is to equip upper-class students of Madrasah Ibtidaiyah Nurul Islam with training and development of strengthening character education (PPK) based on school culture. The method used in this service activity consists of several stages, namely; preparation, implementation, data collection and evaluation. The implementation of strengthening character education is carried out mainly using four (4) ways, namely: 1) Integrating into the curriculum such as the preparation of a Learning Implementation Plan (RPP) for each subject by considering the uniqueness of the identity of the school culture and the surrounding environment and integrating into the construction of teaching materials specifically for each subject that contains references to local culture, 2) Improving the strengthening of school culture-based character education into the learning activity process by integrating it into the curriculum, optimizing local content and classroom management/ management, 3) Strengthening school culture-based character education (PPK) formed through habituation or orientation of daily values, good attitudes of educators, norms, rules, school ecosystems, and school traditions, and 4) Strengthening school culture-based character education with involving or collaborating with the community and through the involvement of existing partners, such as: parents, religious leaders/ leaders, community leaders, educational activists, academics, culturalists, business actors, literati, artists and other related parties. Abstrak Tujuan pengabdian ini adalah membekali siswa kelas atas Madrasah Ibtidaiyah Nurul Islam dengan pelatihan dan pengembangan penguatan pendidikan karakter (PPK) berbasis kultur sekolah. Adapun Metode yang digunakan pada kegiatan pengabdian ini terdari dari beberapa tahapan yaitu; persiapan, pelaksanaan, pengambilan data dan evaluasi. Pelaksanaan penguatan pendidikan karakter dilaksanakan terutama menggunakan empat (4) cara, yaitu: 1) Mengintegrasikan ke dalam kurikulum seperti penyusunan Rencana Pelaksanaan Pembelajaran (RPP) pada setiap mata pelajaran dengan mempertimbangkan keunikan identitas kultur sekolah dan lingkungan sekitarnya dan mengintegrasikan ke dalam konstruksi bahan ajar khusus mata untuk setiap mata pelajaran yang memuat referensi kultur lokal, 2) Meningkatkan penguatan pendidikan karakter (PPK) berbasis kultur sekolah ke dalam proses kegiatan pembelajaran dengan mengintegrasikannya ke dalam kurikulum, mengoptimalkan muatan lokal serta pengelolaan/manejemen kelas, 3) Penguatan pendidikan karakter berbasis kultur sekolah terbentuk melalui kegiatan pembiasaan atau orientasi nilai-nilai sehari-hari, suri tauladan pendidik, norma, aturan, tradisi sekolah dan eksistem sekolah, dan 4) Memperkuat pendidikan karakter berbasis kultur sekolah dengan mellibatkan atau kolaborasi masyarakat serta melalui pelibatan mitra yang ada, seperti: orang tua, pemuka/tokoh agama, tokoh masyarakat, pegiat pendidikan, akademisi, budayawan, pelaku usaha, sastrawan, seniman dan pihak terkait lainnya.